Superior General Br. Armin Luistro, FSC (2022 – 2028) - Hudtohan, Emiliano T. (International Journal of Management and Education in Human Development, 2022)
The shift in power and influence from the West to the East has been predicted by Ian Morris in terms of 1. Energy capture, 2. War making capability, 3. Organization, and 4. Information technology. Kishmore Mahbubani affirms that the New Asian Hemisphere is participating in global power In the context of a volatile, uncertain, complex and ambiguous (VUCA) global situation, Mahbubani and Sng assert that the Association of South East Asian countries (ASEAN) is becoming a catalyst for peace. The election of Br. Armin Luistro, FSC as the 25th Superior General of the Brothers of the Christian Schools symbolizes the rise into power of an Asian, managing a global organization of Western origin. The Philippines as a colony of Spain and America has become a country on its own. The De La Salle Brothers of 1911 were Americans and Europeans; later on De La Salle Philippines is managed by Filipino Brothers. d Br. Benildo Feliciano, FSC, Br. Victor Franco, FSC, Br. Ray Suplido, FSC, and Br. Ricardo Laguda, FSC became general councilors; they are the precursors of Filipino participation in global governance of the Institute of the Brothers of the Christian Schools. Br. Armin Luistro, FSC as Superior General manifests the new Filipino Asian leadership in a Western religious educational organization founded by St. John Baptist de la Salle